BDSM and the Complexity of Consent: Navigating Inclusion and Exclusion - Ofer Parchev (Sexes)
Consent is a foundational component of BDSM (Bondage/Discipline, Dominance/Submission, Sadism/Masochism). It distinguishes non-normative, consensual practices from instances of abuse and exploitation. Its centrality within BDSM, however, underscores the complexity of consent as a constitutive mechanism that facilitates varied intersubjective engagements, from continuous negotiation and aftercare to the use of safe words. The ontological basis of consent within BDSM relies on a model of subjective autonomy wherein individuals actively shape their desires and boundaries within a consensual framework. This paper argues that a significant motivation for many BDSM practitioners lies in the desire to subvert autonomy by engaging in acts that challenge traditional consent boundaries. However, reliance on a purely liberal interpretation of consent often marginalizes such subversive expressions, thereby pushing certain BDSM practices and individuals toward pathological or criminal categorization. Here, I propose an ethical framework grounded in a liberal consent model, which is open to the inclusion of these marginalized practices, thus, fostering a more inclusive understanding of BDSM subjectivity.